2007
DOI: 10.1089/vim.2006.0112
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Induction of Mouse Immune Responses to Hepatitis C Virus by Viral Core Protein-Carrying AttenuatedSalmonella typhimurium

Abstract: Hepatitis C virus (HCV) core protein is considered to be an attractive candidate for inclusion in a protective vaccine. However, this protein may attenuate the development of systemic immune responses because of its immunomodulatory properties. In this study, a eukaryotic expression plasmid, pCI-C, and an in vivo-inducible prokaryotic expression plasmid, pZW-C, for HCV core protein were constructed and transformed into attenuated Salmonella typhimurium aroA strain SL7207. The recombinant expression plasmids SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…Cell proliferation was assayed using the CellTiter 96 AQueous One Solution. The stimulation index (SI) was determined as described previously (33). PBMCs at a concentration of 2Â10 6 /mL were cultured in complete RPMI 1640 medium in the presence of various plasmids (final concentration 10 mg/mL) in a 5% CO 2 -humidified incubator at 378C.…”
Section: Pbmc Isolation and Stimulation Using Cpg Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell proliferation was assayed using the CellTiter 96 AQueous One Solution. The stimulation index (SI) was determined as described previously (33). PBMCs at a concentration of 2Â10 6 /mL were cultured in complete RPMI 1640 medium in the presence of various plasmids (final concentration 10 mg/mL) in a 5% CO 2 -humidified incubator at 378C.…”
Section: Pbmc Isolation and Stimulation Using Cpg Plasmidsmentioning
confidence: 99%
“…Serial dilutions of the effector cells were cultured with 2Â10 3 SP20/S target cells in 96-well round-bottom plates and incubated for 6 h at 378C with 5% CO 2 . HBsAg-specific CTL activity was measured by lactate dehydrogenase (LDH) release using the nonradioactive cytotoxicity assay kit (Cytotox 96; Promega Corp., Madison, WI) as described previously (33). The OD 492 absorbance values of the culture supernatants were measured on an ELISA microplate reader, and cell-specific lysis was calculated according to the following formula: (experimental release -spontaneous release) / (total releasespontaneous release)Â100%.…”
Section: Cytokine Assaymentioning
confidence: 99%
“…We have shown that plasmids directing higher levels of core expression were less immunogenic than directing lower levels of HCV core expression [5]. Several studies observed that transient expression of HCV core interferes with the induction of cellular immune responses against co-delivered genes [15,16]. In lines with these findings, mice transgenic for HCV core demonstrated significantly diminished T-lymphocyte responses compared to their non-transgenic littermates [17], and could not adequately respond to viral infections [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Safety of HCV core preparations in the human trials paved the way to the continuous efforts to improve its immunogenic performance. Promising results were obtained with the chimeras of HCV core protein with HBV precore regions [47], tetanus toxoid [48], HCV core carried by Lambda phage nanoparticles [49] or an attenuated Salmonella strain [15], demonstrating the possibility to overcome core-driven immune suppression.…”
Section: Introductionmentioning
confidence: 99%
“…Assim sendo, os genes heterólogos são clonados em plasmídios asd positivos e estes, utilizados para transformar células ∆asd de Salmonella. Animais imunizados com tais linhagens recombinantes são colonizados somente por bactérias contendo o plasmídio e, portanto, expressando o antígeno heterólogo (BRANGER et al, 2009).Linhagens atenuadas de Salmonella são ótimas candidatas a vacinas orais, via pela qual apresenta muitas vantagens de aplicação em relação a outras(LIAO et al, 2007;LI et al, 2008;WANG et al, 2009), e que vem sendo constante foco de estudo(SMOLEN et al, 2010). Após administração oral, linhagens de S. enterica aderem e invadem células da mucosa intestinal, preferencialmente células M (JONES; GHORI; FALKOW, 1994), e atingem os sítios linfóides das placas de Peyer (PP) e/ouGALT (CARTER;COLLINS, 1974;HUANG;HAJISHENGALLIS;MICHALEK, 2000).…”
unclassified